1997
DOI: 10.1063/1.364932
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lamination on soft magnetic properties of FeN films on sloping surfaces

Abstract: We have found that the soft magnetic properties of FeN/AlN laminated films do not degrade on sloping surfaces. The easy axis coercivities of FeN/AlN multilayer films are approximately 1.5 Oe and have little variation with slope angle, α. The anisotropy fields slightly vary from 13 to 17 Oe when the slope angles (α) change from 0° to 60°. In contrast, single layer FeN films show a significant degradation of soft magnetic properties with the slope angle. Residual stress does not have a significant correlation wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…8, where and indicate scattering vectors for the planes. This result was similarly observed in the synchrotron X-ray diffraction experiments done by Sin et al [5], which produce a smaller defocusing error at higher pole distances. They observed strong (110) peaks at a of 20 , 60 , and 150 when the incident atomic-flux angle was at 135 , which corresponds to an oblique-incident angle of 45 .…”
Section: B Microstructuressupporting
confidence: 82%
See 1 more Smart Citation
“…8, where and indicate scattering vectors for the planes. This result was similarly observed in the synchrotron X-ray diffraction experiments done by Sin et al [5], which produce a smaller defocusing error at higher pole distances. They observed strong (110) peaks at a of 20 , 60 , and 150 when the incident atomic-flux angle was at 135 , which corresponds to an oblique-incident angle of 45 .…”
Section: B Microstructuressupporting
confidence: 82%
“…Researchers have shown that these materials can function as write poles [1], [2], even though several problems still need to be solved. In particular, the neck region of a head slider made from the Fe-based nitride materials has shown magnetic degradation due to oblique-incident deposition [3]- [5]. The resulting low permeability and high coercivity have led to poor head efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…This has been seen to have the additional benefit of improving the softness and anisotropy of these films, as well as minimizing the previously reported degradation of magnetic properties and efficiency of sputtered materials on topography, as found on the hill region of TFH writers. [4][5][6][7] …”
Section: Introductionmentioning
confidence: 99%
“…A four-circle X-ray diffractometer is used to acquire the [3] and lamination [4] have been investigated to attain soft magnetic properties of Fe or Fe-based nitride films on a sloping surface.…”
Section: Introductionmentioning
confidence: 99%